Architectural education through materiality : pedagogies of 20th century design - Couchez, Elke; Heynickx, Rajesh, 1977- (Abingdon, Oxon ; New York : Routledge, 2022)
"What kind of architectural knowledge was cultivated through drawings, models, design-build experimental houses and learning environments in the 20th century? And, did new teaching techniques and tools foster pedagogical, institutional and even cultural renewal? Architectural Education Through Materiality: Pedagogies of 20th Century Design brings together a collection of illustrated essays dedicated to exploring the complex processes that transformed architecture's pedagogies in the 20th century. The last decade has seen a substantial increase in interest in the history of architectural education. This book widens the geographical scope beyond local school histories and sets out to discover the very distinct materialities and technologies of schooling as active agents in the making of architectural schools. Architectural Education Through Materiality argues that knowledge transmission cannot be reduced to 'software', the relatively easily detectable ideas in course notes and handbooks, but also has to be studied in close relation to the 'hardware' of, for instance, wall pictures, textiles, campus designs, slide projectors and even bodies. Presenting illustrated case studies of works by architects, educators and theorists including Dalibor Vesely, Dom Hans van der Laan, Alessandro Mendini, Heinrich Wölfflin, Alfons Hoppenbrouwers, Joseph Rykwert, Pancho Guedes and Robert Cummings, and, focusing on student-led educational initiatives in Europe, the UK, North America and Australia, the book will inspire students, educators and professionals with an interest in the many ways architectural knowledge is produced and taught"--
Objects on display : learning through looking -- Hands-on : learning through manual work -- Bodies in space : synesthetic learning -- Learning by technologies : audio-visual transmissions.
Includes bibliographical references and index.
Keywords: Architecture -- Study and teaching -- History -- 20th century; Learning, Psychology of -- History -- 20th century